2014
DOI: 10.1007/s00467-014-2806-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary citrate excretion in healthy children depends on age and gender

Abstract: BackgroundHypocitraturia is considered a major risk factor for calcium stone formation. However, there is no widely accepted reference database of urinary citrate excretion in children. The aim of our study was to determine the amount of citrate eliminated in the urine over a 24-h period in a pediatric cohort and to determine an optimal unit reflecting excretion.MethodsThe study cohort comprised 2,334 healthy boys and girls aged 2–18 years. The levels of urinary citrate were assessed by an enzymatic method in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 22 publications
4
27
0
1
Order By: Relevance
“…Specifically, urinary citrate levels increase with age only in females. According to this, boys excrete less citrate than girls, at the beginning of puberty, suggesting that citrate excretion could be influenced by sexual hormones [40]. The importance of sexual hormones is also confirmed by data obtained in pre and postmenopausal women [41][42][43].…”
Section: Discussionsupporting
confidence: 61%
“…Specifically, urinary citrate levels increase with age only in females. According to this, boys excrete less citrate than girls, at the beginning of puberty, suggesting that citrate excretion could be influenced by sexual hormones [40]. The importance of sexual hormones is also confirmed by data obtained in pre and postmenopausal women [41][42][43].…”
Section: Discussionsupporting
confidence: 61%
“…Women typically excrete more citrate than men, as was shown in the present study by the average citrate excretion in women being higher than in men in the non-citrate group at both study initiation and at the 1-year follow-up point (P < 0.03 and P < 0.04, respectively, paired t-test). 26 The results also showed that there were no significant differences between the two patient groups with respect to the ratios of female patients experiencing microcalculi enlargement. In the non-citrate group, suppression of microcalculus enlargement was considered to be a result of high citrate excretion levels.…”
Section: Discussionmentioning
confidence: 86%
“…Various domestic and international studies have confirmed that the etiology of UC is closely related to environmental factors (Finlayson, 1974;Embon et al, 1990;Leusmann et al, 1990), as well as to genetic factors, ethnicity, gender, age, dietary habits, urinary biochemical abnormalities, etc. (Siener, 2006;Park et al, 2010;Kirejczyk et al, 2014). Previous reports (Nishijima et al, 2002;Lin et al, 2011) have stated that polymorphism of the vitamin D receptor gene is also related to the development of UC.…”
Section: Introductionmentioning
confidence: 99%